The expression of late Cenomanian–Coniacian episodes of accelerated global change in the sedimentary record of the Mexican Interior Basin. (March 2023) - Colín-Rodríguez, Azucena; Núnez-Useche, Fernando; Adatte, Thierry; Spangenberg, Jorge E.; Omaña-Pulido, Lourdes; Alfonso, Pura; Pi-Puig, Teresa; Correa-Metrio, Alexander; Barragán, Ricardo; Martínez-Yáñez, Mario; Enciso-Cárdenas, Juan Josué
Abstract: Climate and oceanographic changes during the Oceanic Anoxic Event 2 (OAE 2) and the Late Turonian–Coniacian Event (LTCE) are reported from a succession deposited in the central part of the Mexican Interior Basin, based on sedimentological, microfacies, mineralogical, and geochemical analysis. Typical δ 13 C positive excursions that characterize both the OAE 2 and the LTCE were identified. Organic-rich sediments during the initial stage of OAE 2 (before and around peak "A", late Cenomanian) and the middle stage of LTCE (around the Hitchwood event) accumulated under increasingly warm and humid conditions, as evidenced by high chemical index of alteration values. Elevated concentrations of detrital proxies coupled with high phosphorus mass-accumulation rates suggest that this scenario led to a rise in detrital and nutrients fluxes that induced eutrophication and anoxic/dysoxic bottom waters. Eutrophic-anoxic/dysoxic marine conditions are further supported by the highest TOC values, coinciding with significant enrichments in redox- and productivity-sensitive trace elements. Moreover, these conditions can also be inferred from the abundant presence of radiolarians and filaments in the OAE 2 interval, and the occurrence of opportunistic foraminifera in the LTCE interval. Oxygen-depleted bottom waters are also indicated by Mo–U systematics. The onset of the Mexican Orogen tectonic uplift and increased upwelling strengthened the transference of nutrients, enhancing organic matter burial during the initial stage of OAE 2. In the mid-OAE 2 δ 13 C trough interval (between peaks "A" and "B") equivalent to the Plenus Cold Event, bioturbated sediments with low TOC values accumulated during a short episode of cold climate conditions probably reflecting the southward flow of boreal water throughout the Mexican Interior Basin. The minimum δ 34 Spy value occurring within the OAE 2 interval in the Mexican Interior Basin is lower than elsewhere because of a local increase in sulfate concentrations. Highlights: Environmental changes related to the OAE 2 and the LTCE are recognized. Eutrophic-anoxic/dysoxic conditions developed during global warming phases. Both regional/local and global forcing factors controlled organic matter deposition. Local weathering enhanced marine sulfate concentrations.